A New Saturn Model of Ionospheric Transport and Electrodynamics (SMITE) - Omakshi Agiwal; Luke Moore; Carlos Martinis; Ingo Mueller-Wodarg; J.D. Huba (The Planetary Science Journal)
We introduce the Saturn Model of Ionospheric Transport and Electrodynamics (SMITE), a new model that incorporates interhemispheric plasma transport using a dipole magnetic field aligned grid, and a range of dynamic processes that influence Saturn’s ionosphere. SMITE includes tunable parameters for the inflow of exogenous material, seasonal and local time atmospheric variations, the ring shadow, and plasma transport driven by neutral winds and low-latitude electrodynamics. SMITE is an adaptation of the terrestrial SAMI2 model, which has successfully reproduced numerous ionospheric phenomena at Earth. Preliminary results show that SMITE can reproduce latitudinal trends in the total electron content and altitudinal electron density distributions observed by the Cassini spacecraft. Model–data comparisons also show that diurnally variable low-latitude electrodynamics may intermittently be active at Saturn. SMITE is also the first model to show that strong plasma density gradients, such as those caused by Saturn’s ring shadow in the winter hemisphere, drive interhemispheric field-aligned transport from the sunlit hemisphere to the winter hemisphere, which has previously been hypothesized from Cassini spacecraft measurements. Future applications will use SMITE to analyze data from the Cassini mission in detail and investigate the influence of Saturn’s magnetic field on the structure of its ionosphere. These investigations will provide the first insights into the role of nonauroral electrodynamics at a giant planet, thus advancing our broader understanding of giant planet ionospheres.